EFL Speaking Anxiety in Higher Education: Factors, Impacts, and Interventions - Dian Fera Pratiwi; Sultan Baa; Muftihaturahmah Burhamzah; Chuzaimah; Nur Ima (Universitas Sulawesi Barat, 2026)
Speaking anxiety remains a persistent affective barrier to oral language development in English as a Foreign Language (EFL) higher education, particularly in Indonesian universities where authentic communication opportunities are limited. Grounded in the Foreign Language Classroom Anxiety (FLCA) framework, this systematic literature review synthesizes the contributing factors, learning impacts, and instructional interventions related to speaking anxiety among EFL university students. Following the PRISMA framework, the review searched Google Scholar, Scopus, Web of Science, ERIC, and manual reference tracking. From 110 initial records, a four-stage screening process yielded 50 peer-reviewed studies published between 2015 and 2026. Data were analyzed through thematic analysis using open, axial, and selective coding. Findings show that speaking anxiety emerges from interacting linguistic (e.g., vocabulary limitations, grammatical difficulties, pronunciation issues, and L1 interference), psychological (e.g., low self-confidence, shyness, and fear of negative evaluation), and situational factors (e.g., evaluative classrooms, time pressure, and unsupportive social dynamics). These factors reinforce avoidance behaviors that hinder communication, participation, cognitive processing, and long-term language proficiency. Four intervention categories were identified: cognitive-affective strategies, social-collaborative approaches, pedagogical redesign, and technology-assisted learning, including AI-based tools. However, implementation remains constrained by limited learner autonomy, time pressures, and unequal digital access. This review demonstrates that mitigating speaking anxiety in EFL higher education requires pedagogical designs that systematically combine scaffolded speaking tasks, psychologically supportive feedback practices, peer-collaborative interaction, and equitable integration of technology-assisted rehearsal tools. By synthesizing fragmented evidence across linguistic, psychological, and contextual dimensions, the study contributes a comprehensive framework for understanding speaking anxiety as both an individual affective challenge and a structurally mediated educational issue. These findings provide a practical evidence base for EFL educators and curriculum designers to develop context-responsive interventions that enhance learners’ oral participation, confidence, and long-term communicative competence.